Perancangan Exhaust Fan dengan Kontrol Kecepatan Otomatis dan Ventilasi Otomatis Berbasis Suhu dengan Mikrokontroler - Adfa Alfiansyah, Achmad; Budihardjo, Rafiel Syafa; Prasetyo, Muhammad Emery; Akbar, Alifsyah; Muslimin, Muslimin; Luqyana, Dhiya; Milah Muhamad, Azam (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
As a tropical country, Indonesia often faces hot air temperatures, affecting indoor comfort, including restaurants and cafes. This condition requires the development of technology that can maintain air circulation efficiently and adaptively. Conventional exhaust fans are often not compelling enough because they cannot adjust their operations to changes in environmental conditions automatically. This study uses a microcontroller to develop an automatic speed control system for exhaust fans and automatic ventilation to overcome this temperature and humidity problem. This system uses temperature and humidity sensors to detect environmental conditions, regulate fan speed with a motor driver, and control automatic ventilation via a servo motor. This system design has been realized and has been tested. The experimental results show that the system can work according to the desired parameters, provide an efficient solution for temperature and humidity control, and has the potential to be applied in various environments, especially in restaurants and cafes that require optimal air comfort.